Pengelolaan Keuangan Dana Pendidikan Anak Pada Keluarga Buruh Peternakan Ayam Petelur Desa Kawedusan Kecamatan Ponggok Kabupaten Blitar - Nurin Lailatul Hidayah; Syahrul Munir (Jurnal Pendidikan Ekonomi, 2021)
This study aims to determine the financial management of education funds carried out by chicken farm workers. The data in this study were collected using a qualitative descriptive method. The results showed that the financial management of children's education funds carried out by livestock workers was classified as poor. This is due to a lack of basic knowledge about finance, which is still classified as non literate. So that long-term needs such as children's education are not planned properly, the financing of children's education is carried out spontaneously without being prepared in advance. Most of the income they earn is allocated for daily consumption needs, so they do not plan for children's education savings. DOI: https://dx.doi.org/10.17977/UM014v14i22021p152